Berliner chic : a locational history of Berlin fashion - Ingram, Susan (Susan V.) (Intellect ; University of Chicago Press, 2011)
Since becoming the capital of reunited Germany, Berlin has had a dose of global money and international style added to its already impressive cultural veneer. Once home to emperors and dictators, peddlers and spies, it is now a fashion showplace that attracts the young and hip. This gripping history follows Berlin chic through a host of historical eras and events, including the Nazi eradication of the primarily Jewish ready-to-wear industry, the confusion surrounding the split and reunification of the East and West, an unsuccessful effort to launch a fashion museum, and the debut of Berlin Fashion Week in 2007. There are many fabulous stories to tell about Berlin fashion and Berliner Chic tells them all with verve and considerable expertise.